The Influence of Hand Tool Design on Hand Grip Strength: A Review - Halim, Isa; Radin Umar, Radin Zaid; Syed Mohamed, Muhammad Syafiq; Ahmad, Nadiah; Padmanathan, Vinothini; Saptari, Adi (International Journal of Integrated Engineering, 2019)
Hand is made up of bones, tendons, ligaments, nerves and blood vessels that can be easily debilitated and injured if the hand tool is not design ergonomically. Recently researchers have examined the effects of individual, environmental and occupational factors on hand grip strength. However, information on the influence of hand tool design on hand grip strength is still lacking. The aim of this paper is to provide a comprehensive review of factors influencing hand grip strength focusing more towards hand tool design factors. The authors searched the journal articles, book and guidelines from the online databases of Google Scholar, ScienceDirect and Pubmed. Fourteen factors of hand tools design were found to have significant effect on the hand grip strength. The handle size shows the most significant factor for hand grip strength.